A metal‐organic framework ZJU‐136‐Ce for combined chemotherapy and chemodynamic therapy. Issue 9 (27th December 2021) - Lei, Chen; Yang, Xue; Huang, Xiajuan; Yu, Shijiang; Zhu, Hongliang; Lin, Wenxin; Mou, Xiaozhou
Abstract: A metal‐organic framework ZJU‐136‐Ce with ideal water stability was synthesized. It was adopted to load Mn 2+ and DOX for chemo/chemodynamic therapy of tumor, the loading capacity of Mn 2+ and DOX was 0.87 wt % and 10.19 wt % in ZJU‐136‐Ce, respectively. DOX&Mn@ZJU‐136‐Ce exhibited significant effects of inhibition of Hela cell growth, which confirmed it had a potential application prospect in the multimodal cancer therapy. Abstract :